Body composition profiling and obesity analysis of healthy adults: a cross-sectional study - Zara Khalid; Muhammad Naveed Babur; Furqan Ahmed Siddiqi; Sana Khalid; Muhammad Ali Arshad Tareen; Naureen Tassadaq (Journal of the Pakistan Medical Association, 2022)
Obesity as depicted by changes in the body composition is considered a global epidemic of the 21st century, predisposing to cardiometabolic diseases. This analytical cross-sectional study evaluated body composition parameters in both genders and conducted an obesity analysis of healthy adult Pakistani population. Using non-probability purposive sampling technique, data was collected from 205 healthy adults (aged 18-45 years), who had not been participating in any structured exercise or dietary regime over the last six months. Body composition was assessed using bioelectrical impedance analyser. For data analysis, descriptive statistics, Mann-Whitney U-test and one-sample T-test were applied. The mean body mass index was 24.3±4.93 kg/m2. Body composition components which were significantly higher in males included soft lean mass, fat-free mass index, skeletal muscle mass index and bone mineral content, whereas females had significantly higher percentage of body fat (PBF), visceral fat area and fat mass index (p<0.05). —Continue